Constructing Forecast Confidence Bands During the Financial Crisis - Clinton, Kevin (IMF Working Papers; Working Paper ;, 2009)
We derive forecast confidence bands using a Global Projection Model covering the United States, the euro area, and Japan. In the model, the price of oil is a stochastic process, interest rates have a zero floor, and bank lending tightening affects the United States. To calculate confidence intervals that respect the zero interest rate floor, we employ Latin hypercube sampling. Derived confidence bands suggest non-negligible risks that U.S. interest rates might stay near zero for an extended period, and that severe credit conditions might persist.